An analysis of the factors behind the citizen’s attitude of rejection towards tourism in a context of overtourism and economic dependence on this activity - Martín Martín, José María; Salinas Fernández, José Antonio; Guaita Martínez, José Manuel (Sustainability, 2019)
New tourism trends, such as vacation rentals websites and low-cost tourism, have generated a new environment of interactions between tourism and the citizens. To this, we must add the fortuitous increase in demand in some touristic destinations. This has derived in situations of rejection in traditionally tourism-dependent environments. In this study, which is focused on the city of Barcelona, we use work-field data to analyze the elements that lie behind the popular aversion to tourism. Assuming a non-forced analysis that takes the Social Exchange Theory as a framework, we have determined that the negative economic effects derived from the increase in the number of accommodations destined for vacation rentals and in the demand lie behind this rejection. The main impacts that are perceived directly from these factors are: the increase in residential rentals prices and a shift from a traditional market to one oriented to the tourist with higher prices. It has also been determined that the most vulnerable population groups are those who manifest a stronger rejection, tenants of apartments in city centers, and citizens with a low/medium income, who perceive rises in the prices and a change in the market focus to a larger extent.
Keywords: social sustainability; tourism; sharing economy; economic impacts; overtourism; anti-tourism movements; tourism-phobia; JCR; Scopus